2020
DOI: 10.1097/mao.0000000000002651
|View full text |Cite
|
Sign up to set email alerts
|

Initial Degree of Spontaneous Nystagmus Affects the Length of Hospitalization of Patients With Vestibular Neuritis

Abstract: Objective: To assess factors predicting vestibular neuritis (VN) prognosis at an early stage. Study Design: Retrospective chart review. Setting: University hospital. Patients: Sixty-five patients with VN, between 2014 and 2018. Interventions: Bithermal caloric test, rotatory chair test, subjective visual horizontal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The explanation might be that SN is the most prominent indicator of static vestibular imbalance. Previous study has found that initial degree of SN affects the duration of hospitalization, and VN patients with higher SN degree at the initial evaluation tended to have persistent SN [23]. VN patients with lower occurrence of SN experienced mild vestibular syndromes since their static imbalance was incompletely damaged or quickly recovered.…”
Section: Discussionmentioning
confidence: 85%
“…The explanation might be that SN is the most prominent indicator of static vestibular imbalance. Previous study has found that initial degree of SN affects the duration of hospitalization, and VN patients with higher SN degree at the initial evaluation tended to have persistent SN [23]. VN patients with lower occurrence of SN experienced mild vestibular syndromes since their static imbalance was incompletely damaged or quickly recovered.…”
Section: Discussionmentioning
confidence: 85%
“…The presentation of significant spontaneous nystagmus is associated with hospitalization for ≥5 days and nystagmus persisting at 1 month after discharge (with a cutoff of 12.1°/s) in patients with vestibular neuritis (VN). 13 Two of three patients with delayed endolymphatic hydrops showed a typical horizontal-torsional nystagmus beating to the healthy side, whereas the third showed initial upbeat nystagmus with a slight torsional component that evolved into horizontal-torsional nystagmus beating to the healthy side. Initial upbeat nystagmus might reflect inhibition of the superior semicircular canal in the involved ear.…”
Section: General Findingsmentioning
confidence: 96%